Synthesis of 2,1-benzisoxazole-3(1H)-ones by base-mediated photochemical N–O bond-forming cyclization of 2-azidobenzoic acids - Dzhons, Daria Yu.; Budruev, Andrei V. (Beilstein Journal of Organic Chemistry, 2016)
The base-mediated photochemical cyclization of 2-azidobenzoic acids with the formation of 2,1-benzisoxazole-3(1H)-ones is reported. The optimization and scope of this cyclization reaction is discussed. It is shown that an essential step of the ring closure of 2-azidobenzoic acids is the formation and photolysis of 2-azidobenzoate anions.
Keywords: aryl azides; azepinones; 2,1-benzisoxazolones; 1,5-electrocyclization; nitrenes; photochemical cyclization